PENGARUH SENAM PROLANIS (PROGRAM PENGELOLAAN PENYAKIT KRONIS) TERHADAP PENURUNAN TEKANAN DARAH KLIEN HIPERTENSI DI KLUB PROLANIS PUSKESMAS GRIYA ANTAPANI - Pratama, Oktarian; Aisah, Siti (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
Hypertension, commonly referred to as high blood pressure, is defined as having a systolic blood pressure >140 mmHg or a diastolic blood pressure >90 mmHg. In Indonesia, hypertension is one of the leading non-communicable diseases, with a reported 185,857 cases. Prolanis exercise is a non-pharmacological treatment method for reducing blood pressure, organized by BPJS Kesehatan. In the Prolanis Club at the Griya Antapani Health Center, there are 150 members diagnosed with hypertension. This study aims to determine the effect of Prolanis Exercise (Chronic Disease Management Program) on lowering blood pressure in patients with hypertension. This is a quasi-experimental study with a one-group pretest-posttest design. The sample consisted of 20 members of the Prolanis Club, selected using purposive sampling. Data collection was conducted using observation sheets, sphygmomanometers, and stethoscopes. The results, analyzed using the Wilcoxon test, showed that Prolanis exercise had a significant effect on reducing blood pressure. The average blood pressure before participating in Prolanis exercise was 146.50/96.00 mmHg, while after the exercise, it was 127.50/82.50 mmHg. The results of statistical tests obtained a p value of 0.001 (<0.05), so it can be concluded that there is a significant effect of prolanis exercise (chronic disease management program), indicating a significant effect on blood pressure and a significant difference between pre- and post-intervention measurements. It is recommended that nurses at health centers incorporate Prolanis exercise into their regular programs to improve the quality of life for patients with hypertension.